The Impact of Generation Z's Financial Literacy and Digital Payment Adoption on Local Economic Development - Putri Irmala Sari; Supri Yanto (Universitas Negeri Yogyakarta, 2026)
This study investigates the underexplored nexus between the micro-financial behaviors of Generation Z and macroeconomic outcomes within the Indonesian context. Despite their growing economic influence, empirical evidence linking Gen Z's financial capabilities and digital payment usage to tangible local economic development remains scarce. This research aims to fill this gap by quantitatively analyzing the simultaneous impact of financial literacy and digital payment adoption on local economic development indicators. Employing a quantitative design, primary data were collected via a survey of Indonesian Gen Z individuals. The findings reveal that both heightened financial literacy and robust digital payment adoption exert a statistically significant, positive influence on local economic development. Notably, digital payment adoption demonstrates a slightly stronger effect, underscoring the transformative role of transactional efficiency. Theoretically, this study bridges behavioral finance and economic development theory. In practice, it offers crucial insights for policymakers and financial educators, suggesting that targeted programs to enhance financial literacy and digital infrastructure for youth can serve as potent catalysts for sustainable regional economic growth.